Pengaruh Model Pembelajaran RADEC dengan Media Gambar Animasi Terhadap Berpikir Kreatif dan Kemampuan Menulis Cerita Pendek Siswa SD - Isma Irawati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Creative Thinking Ability is the skill of solving a problem according to one's own thoughts so as to form something new. Writing is the process of expressing ideas through language to the reader. The results of interviews conducted with class VI teachers of SDN Wonocepokoayu 01 regarding short story writing skills, there are several difficulties faced by students, namely that there are still some students who are less creative in writing stories. The RADEC learning model is a learning model that allows students to learn on their own before learning in class. In this study, there are two classes that will see the effect of the RADEC learning model on creative thinking skills and short story writing skills. The control class is students of SDN Bedayu and the experimental class is students of SDN Wonocepokoayu 01. In the creative thinking ability indicator, the post-test score for the experimental class was 1.921 and the control class was 1.345. The average score for the experimental class was 76.84 and the average score for the control class was 53.8. After the t-test, a significance value of less than 0.05 (p <0.05) was obtained, namely a significance value of 0.000. In the short story writing skill indicator, the post-test value of the experimental class was 2.076 and the control class was 1.717. The average value of the experimental class was 83.1 and the average value of the control class was 63.8. After the T-test, a significance value of less than 0.05 (p <0.05) was obtained, namely a significance value of 0.000. Because it obtained a significance value of 0.000, there was a significant influence on the indicators of creative thinking skills and short story writing skills in the experimental class after using the RADEC learning model.
:: Finalisasi Repositori File 3 Juni 2026_Kurnadi
Keywords: Creative Thingking; Short Story Writing; RADEC